Michel Charles en quatre temps: Sur la théorie des textes possibles - Bortier, Camille (Verbum – Analecta Neolatina, 2025)
Michel Charles proposes a form of literary analysis that is not only interested in the text “as it is”, but also explores the possible texts that could have existed. We present Charles’ model and its evolution over time “in four stages”, each corresponding to the publication of one of his books.